Gemcitabine/nab-Paclitaxel versus FOLFIRINOX for palliative first-line treatment of advanced pancreatic cancer: A propensity score analysis. (July 2021) - Riedl, Jakob M.; Posch, Florian; Horvath, Lena; Gantschnigg, Antonia; Renneberg, Felix; Schwarzenbacher, Esther; Moik, Florian; Barth, Dominik A.; Rossmann, Christopher H.; Stotz, Michael; Schaberl-Moser, Renate; Pichler, Martin; et al.
Abstract: Background: Gemcitabine/nab-paclitaxel (GN) and FOLFIRINOX are standard first-line treatment options for advanced pancreatic ductal adenocarcinoma (aPDAC), but currently no prospective randomised head-to-head comparison between these treatments has yet been performed. Methods: We conducted a comparative propensity score (PS) analysis of overall (OS) and progression-free survival (PFS) in a tri-centre cohort of patients with aPDAC undergoing palliative first-line treatment with either GN or FOLFIRINOX. Results: In unadjusted analysis, OS and PFS were highly similar between patients treated with GN (n = 297) and FOLFIRINOX (n = 158). In detail, median, 1- and 2-year OS estimates were 10.1 months, 42% and 18% in the GN group, as compared to 11.2 months, 45% and 12% in the FOLFIRINOX group, respectively (log-rank p = 0.783). Accordingly, median (4.6 versus 4.8 months), 6-month (40% versus 43%) and 1-year (9% versus 9%) PFS estimates did not significantly differ (log-rank p = 0.717). However, patients treated with FOLFIRINOX were significantly younger, had fewer comorbidities, and a better Eastern Cooperative Oncology Group performance status. These imbalances were accounted for by weighting the data with the PS. In PS analysis of survival outcomes, OS and PFS remained comparable between the two treatment groups. In detail, PS-weighted median, 1- and 2-year OS estimates were 10.1 months, 42% and 18% in the GN group, as compared to 10.1 months, 40% and 13% in the FOLFIRINOX group (PS-weighted log-rank p = 0.449). PS-weighted PFS estimates again did not differ (PS-weighted log-rank p = 0.329). Conclusion: This real-world comparative effectiveness study indicates that FOLFIRINOX and GN have similar effectiveness in the palliative first-line treatment of aPDAC. Highlights: Propensity score–adjusted comparative effectiveness analysis. Real-world palliative first-line treatment in advanced pancreatic cancer. FOLFIRINOX and gemcitabine/nab-paclitaxel have similar effectiveness. Findings are consistent across all relevant patient's subgroups.